Rigging for games : a primer for technical artists using Maya and Python - Assaf, Eyal, ....- (Boca Raton : CRC Press, 2016)
Rigging for Games: A Primer for Technical Artists Using Maya and Python is not just another step-by-step manual of loosely related tutorials. Using characters from the video game Tin, it takes you through the real-world creative and technical process of rigging characters for video games and cinematics, allowing readers a complete inside look at a single project. You'll explore new ways to write scripts and create modular rigs using Maya and Python, and automate and speed up the rigging process in your creative pipeline. Finally, you'll learn the most efficient ways of exporting your rigs into the popular game engine Unity. This is the practical, start-to-finish rigging primer you've been waiting for!
Includes bibliographical references and index.
Keywords: Maya (Computer file).; Rigging (Computer animation).; Video games -- Design; Computer games -- Design; Python (Computer program language).